2013
DOI: 10.1021/bi401000e
|View full text |Cite
|
Sign up to set email alerts
|

Acid–Base Catalysis and Crystal Structures of a Least Evolved Ancestral GFP-like Protein Undergoing Green-to-Red Photoconversion

Abstract: In green-to-red photoconvertible fluorescent proteins, a three-ring chromophore is generated by the light-activated incorporation of a histidine residue into the conjugated π-system. We have determined the pH-rate profile and high- and low-pH X-ray structures of a least evolved ancestor (LEA) protein constructed in the laboratory based on statistical sequence analysis. LEA incorporates the minimal number of substitutions necessary and sufficient for facile color conversion and exhibits a maximal photoconversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(110 citation statements)
references
References 44 publications
9
88
0
Order By: Relevance
“…Such deviation is presumably owing to the increased flexibility of the chromophore phenolic ring caused by weakening/disruption of the hydrogen bond to the residue at position 142. These data are in line with the previously proposed mechanism, in which the PC is triggered by excitedstate chromophore motions promoted by a decreased density of molecular packing in the immediate chromophore environment (Kim et al, 2013). However, such an increase in the chromophore mobility often decreases its quantum yield, drastically impacting the usability of the corresponding mutants (Mandal et al, 2004)…”
Section: Discussionsupporting
confidence: 91%
“…Such deviation is presumably owing to the increased flexibility of the chromophore phenolic ring caused by weakening/disruption of the hydrogen bond to the residue at position 142. These data are in line with the previously proposed mechanism, in which the PC is triggered by excitedstate chromophore motions promoted by a decreased density of molecular packing in the immediate chromophore environment (Kim et al, 2013). However, such an increase in the chromophore mobility often decreases its quantum yield, drastically impacting the usability of the corresponding mutants (Mandal et al, 2004)…”
Section: Discussionsupporting
confidence: 91%
“…In subsequent work, we demonstrated that the LEA quantum yield of photoconversion is 1.5 × 10 −3 [ 25 ], a value that is similar to other well-characterized pcFPs. Other experiments demonstrated that among the 13 sites, the substitutions T69A and Y116N and the deletion of Tyr217 were particularly important in promoting red color [ 22 ].…”
Section: Least Evolved Ancestor (Lea) Series Of Pcfps Developed Bymentioning
confidence: 61%
“…Crystal structures of the ancestral protein with and without the red-shifting substitutions showed that these residues have virtually no effect on the overall geometry of the structure (46). But molecular dynamics simulations of these proteins suggested that the key substitutions allow a transient intermediate conformational step to be occupied that makes incorporation of the imidazole into the red chromophore possible; specifically, the chromophore must undergo a light-activated internal twist that organizes the surrounding functional groups properly relative to the histidine (45, 46). The derived residues at the 11 other key sites make the backbone around the chromophore flexible and enable this conformation to be accommodated (46).…”
Section: Evolutionary Analysis Narrows Sequence and Structural Searchmentioning
confidence: 99%
“…The derived residues at the 11 other key sites make the backbone around the chromophore flexible and enable this conformation to be accommodated (46). In the ancestral state, the backbone is more rigid and would clash with the twisted intermediate chromophore, so the imidazole cannot be incorporated, even if the histidine alone were present (45, 46). …”
Section: Evolutionary Analysis Narrows Sequence and Structural Searchmentioning
confidence: 99%